If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 6x + 5x = 72 Combine like terms: 6x + 5x = 11x 6 + 11x = 72 Solving 6 + 11x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 11x = 72 + -6 Combine like terms: 6 + -6 = 0 0 + 11x = 72 + -6 11x = 72 + -6 Combine like terms: 72 + -6 = 66 11x = 66 Divide each side by '11'. x = 6 Simplifying x = 6
| (2x+11z)= | | -1.5+0.25=-4.2+-0.2 | | 3(3n+1)=7(7n+5)+5 | | 27r+(27r+2)=486 | | 57=5x+2x+1 | | 2/3n=5/12 | | 100-3z= | | -40-8n=-6(6n-2)+4 | | 2x^2+12x-32=1008 | | 3x+y=0.9 | | -x-1(5+13x)-10=-6(4x+1)-9 | | t(n)=-3n+2 | | 5n+2n=0 | | 3x+7x+2=92 | | 5+4x+x=10 | | 16z^2-54z+35= | | 6+(2.50x-1)=43.50 | | 8c=-56 | | -1=5+5a-6 | | 250x+1000=12415 | | 0=-7x+7 | | -10x-2(9-x)=4(-2x+5)-12 | | e(n)=-3n+2 | | c+3=6 | | 3x+100-40=540 | | a=y | | 5x^2-210x=0 | | 6t^2-30t-12=0 | | 3x+2+x+4=48 | | (21b-5)-5(4b+4)=-6 | | 3+(n+2)=12 | | (X+8)(-2)=12 |